The calligraphic sign from two- dimensional to the three- dimensional in the art of the show: An analytical reading of Hassan al- Masoudi’s shows - Bin Lasfar, Yousry Zakhamah (Journal of Humanities & Social Sciences, 2019)
My research aimed at studying the aesthetic aspect of the contemporary calligraphic sign via tracing its development and evolution since its creation. Strikingly / Remarkably، the letter becomes far more than a mere symbolic signifier to reach an artistic value unfolding a unique intellectual as well as aesthetic patrimony. In my thesis، I tried to deal with the calligraphic sign as part of the art show، which is not only characterized by its multidisciplinary feature but it also combines myriad artistic styles. Accordingly، this paves the way to renew our artistic vision and become more open onto different civilizations / cultures. Following a profound analytic study، my research tackles the various aesthetic، philosophical and technical aspects of the calligraphic sign as being an icon of exchange and communication which، despite its sacred and symbolic connotation with the Arab- Muslim art، has succeeded to emerge at the heart of the contemporary art show. Therefore، the calligraphic sign reveals the controversy about being deeply engraved in the Arab culture and identity and at the same time interactive with other arts and cultures. Hence، the issue is whether the calligraphic sign will be able، in front of these challenges، to offer a different global and aesthetic discourse that copes with the contemporary variables without neither being distorted nor stripped of its historical identity.